2015
DOI: 10.5564/mjas.v15i2.541
|View full text |Cite
|
Sign up to set email alerts
|

Study of pathogenic bacteria detected in fly samples using universal primer-multiplex PCR

Abstract: (De Vos V, et al., 1998;Dragon, DC, 1995;West, 1951;Markus, 1980;Kasprzak et al, 1981;Akinboade et al., 1984;Iwasa et al., 1999

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…The house fly is known to carry pathogens that can cause serious and life-threatening diseases in humans and animals. Over 100 pathogens including bacteria, viruses, fungi and parasites (protozoans and metazoans) have been associated with the insect [ 8 , 9 ]. Molecular analysis revealed that house flies carry very diverse groups of microorganisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The house fly is known to carry pathogens that can cause serious and life-threatening diseases in humans and animals. Over 100 pathogens including bacteria, viruses, fungi and parasites (protozoans and metazoans) have been associated with the insect [ 8 , 9 ]. Molecular analysis revealed that house flies carry very diverse groups of microorganisms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current study presents 3 bacterial and 3 fungal colonies with distinct morphological characters were identified. Two Gram 36,37 . Authors have paid attention to the bacterial communities of other flies [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…In Equation ( 18), the parameter W 1 denotes the cost for elimination of breeding site, W 2 is the cost for sanitation-based works, W 3 is the cost for installing UV light trap, W 4 is the cost for isolation of infected person, and W 5 is the cost of water purification. Each C i,i∈ [1,5] denotes each control parameter-based cost.…”
Section: Effective Control Framework Considering Multiple Disease Carriersmentioning
confidence: 99%
“…Several existing studies showed that bacteria causing diarrhea are carried by houseflies [ 3 , 4 ] mainly. The house fly, Musca domestica L. , is known to carry pathogens including bacteria, viruses, fungi, and parasites which cause life threatening diseases in humans and animals [ 5 , 6 ]. Houseflies breed in human feces [ 7 ] and the existing studies [ 8 , 9 , 10 , 11 , 12 ] have shown increased incidences of diarrhea during the periods of high fly density.…”
Section: Introductionmentioning
confidence: 99%